Finanšu situāciju izvērtēšana un attīstības perspektīvas uzņēmuma SIA "VIA" - Ivanova, Marina (Latvijas Universitāte, 2008)
Šajā darbā ir analizēta ceļu būves uzņēmuma SIA „VIA” 2005.-2007. gadu saimnieciskā darbība, lai noskaidrotu iemeslus un atrastu risinājumus un noteikt šī uzņēmuma attīstību. Darba pirmā nodaļai ir veltīta uzņēmējdarbības vides raksturojumam. Ir veikta uzņēmuma saimnieciski finansiālās darbības izvērtējums par 2005.-2007. gadiem. Darba pēdējā nodaļa aprēķinātas uzņēmuma apgrozījuma, peļņas un rentabilitātes prognozes. Noslēgumā apkopoti autores secinājumi, kuri radušies darba gaitā un izriet no veiktās finanšu analīzes. Darbs sastāv no trijām nodaļām kopapjoms 66 lpp., iekļautas tas 24 tabulas, 14 attēli, piemēroti 9 pielikumi. Atslēgas vārdi: uzņēmējdarbība, peļņa, rentabilitāte, prognozēšana.

This project contains an analysis of the commercial activity of road building company „VIA” Ltd from 2005-2007 in order to ascertain reasons and to find solutions and to determine the development of this company. The first section of the project is dedicated to a description of the company’s commercial operating environment. An assessment of company’s commercial financial activity has been carried out for the period from 2005-2007. The final section of the project provides a calculation of the company’s turnover and forecasts of its profits and commercial viability. The conclusion contains a summary of the author’s conclusions which she drew during the course of the project and which arise from the financial analysis carried out. The job contains three sections amounting to a total of 66 pages including 24 tables, 14 images and the attachment of 9 appendices. Key words: commercial activity, profit, viability, forecasting.
Estimation and prospects of development of financial situation of enterprise "VIA" Ltd.
Keywords: Ekonomika